Streamflow measurement [electronic resource] - Herschy, Reginald W. (Routledge, 2009)
"Streamflow Measurement deals with all the main methods for measuring the flow in rivers and open channels necessary for the practice of efficient water management. Water is now a major issue in a world of some six-and-a-half billion people where more than one-quarter do not have safe drinking water. Only a fraction of the surface water of the Earth is available to us, in fact less than one percent. Whilst this amount of water available is not changing, any future change due to global warming will be made apparent in river measurement." "The book satisfies the current requirements of the International Organization for Standardization and the European Union's Water directive